Analisis Problematika Pembelajaran Maharah Kitabah dengan Menggunakan Metode PJBL pada Siswa Kelas 5a MIN Salatiga: Penelitian - Farhan Nur Ramdhan; Rina Asih Handayani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Writing Skills (Maharah Kitabah) are one of the essential skills taught in Arabic language learning. The purpose of this learning is to enable students to express their ideas, thoughts, and feelings in written Arabic effectively. Writing skill exercises must always be guided toward learning objectives that align with the established indicators. The teaching of Maharah Kitabah also employs specific learning methods to ensure that the learning process runs optimally, one of which is the Project-Based Learning method. This method aims to encourage students to be active and creative during the learning process. However, every learning activity inevitably encounters certain challenges. Therefore, this study applies a qualitative approach, with data obtained based on real conditions in the field. Data collection techniques in this research include observation and interviews. The study was conducted in Grade 5.